2017
DOI: 10.1080/0886022x.2017.1398667
|View full text |Cite
|
Sign up to set email alerts
|

Long-term renal and overall survival of critically ill patients with acute renal injury who received continuous renal replacement therapy

Abstract: This study showed that impaired kidney function at discharge was shown to be an important risk factor affecting the long-term renal survival rates of critically ill patients with AKI. An eGFR <45 mL/min/1.73 m was an independent risk factor for decreased overall survival and renal survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 51 publications
2
17
1
Order By: Relevance
“…Ling ping et al conclude that sepsis-related AKI and using vasopressors were independent risk factors to increase patients' mortality [20]. Dopamine and norepinephrine are two kinds of common vasopressors widely used in curing all kinds of shocks.…”
Section: Discussionmentioning
confidence: 99%
“…Ling ping et al conclude that sepsis-related AKI and using vasopressors were independent risk factors to increase patients' mortality [20]. Dopamine and norepinephrine are two kinds of common vasopressors widely used in curing all kinds of shocks.…”
Section: Discussionmentioning
confidence: 99%
“…There several studies that had shown that the following factors: age, platelet count, APACHE II score, serum creatinine level, a urine output of <0.05 mL/kg/h the first day, eGFR <45 mL/min, et al were associated with the prognosis of patients with AKI undergoing CRRT [18,19]. Moreover, there was study that reported that BMI was a risk for AKI, but was not associated with prognosis of the patients with sepsis treated with CRRT [20].…”
Section: Discussionmentioning
confidence: 99%
“…Nephrology in the acute care setting is moving into an era of cooperation and interaction between several disciplines to address the complex needs stemming from the patients' multi-faceted problems. We should remember that in most settings, renal replacement therapy in the Intensive Care Units is still associated with at least 50% in mortality rate [10,[16][17][18] obviously, the current status quo of practice (and knowledge) is insufficient and the one thing that cannot be justified is inertia. To mention just a few examples, there is exciting literature emerging on fluid overload and volume determination in critically ill patients with acute kidney injury (AKI) [19][20][21][22], the impact of other organ failures (liver, heart) in AKI [23], on peritoneal dialysis as a viable alternative for continuous renal replacement therapy [24,25] and on the uniqueness of medication dosing in those with critical illness receiving renal replacement therapy [26,27].…”
Section: Greetings To the Readersmentioning
confidence: 99%
“…Our impact factor is currently standing at 1.44 and we look forward to attracting exciting papers on a wealth of issues but focus predominantly on AKI and aspects of critical care nephrology [17,28,29]. None of us went into Medicine hoping to find a boring job, and academic writingso it seems to so many of usis akin to a child's birth: it is immensely joyous and exhilarating to bring something into this world, which never existed before.…”
Section: Greetings To the Readersmentioning
confidence: 99%